The expression you have provided is true because sin 2x = 2*sin x*cos x and cos 2x = (cos x)^2 - (sin x)^2

Let start with (cos x + sin x)/(cos x - sin x)

multiply the numerator and denominator by (cos x + sin x)

=> (cos x + sin x)(cos x + sin x)/(cos x - sin x)(cos x + sin x)

=> (cos x + sin x)^2/(cos x)^2 - (sin x)^2

=> [(cos x)^2 + 2*sin x*cos x + (sin x)^2]/cos 2x

=> (1 + sin 2x)/cos 2x

**This proves that (cos x + sin x)/(cos x - sin x) = (1 + sin 2x)/cos 2x**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now